Water balance - stream water level and discharge from Långbäcken, Catchment 13 - Svartberget Research Station (Swedish University of Agricultural Sciences, 2024)
Stream water level measurements and discharge calculations from streams participating in the SITES Water and station base program including a constantly validated stream discharge relation curve. For further information on calculations and installation read COMMENT in the header of the data set, which guides to related document.
Svartberget Research Station (2024). Water balance - stream water level and discharge from Långbäcken, Catchment 13, 2009-04-28–2023-12-20 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/wBmQMQV3F1PrYKjnwYDrmEg5
Keywords: Svartberget Research Station; Discharge; Inland waters; Stream; Water level gauges; Time instant; Time instant; Stream level; Stream level; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap